Adaptive beam microstrip patch transceiver using artificial switch for RADAR application - Azim Haikal Zianal (School of Computer and Communication Engineering, University Malaysia Perlis, 2015)
In general, most of RADAR antenna is used mechanical RADAR which can propagate the radio frequency (RF) clearly. In this project, the scope is to develop a single circular-sized patch antenna that can operate in range frequency 2.4 GHz until 2.5 GHz by using a Taconic as a substrate material. This Taconic material has be chosen because has low dielectric constant and their thickness can give best efficiency and large bandwidth. The circular-sized patch antenna will be surrounding with two parasitic elements with same shape as the patch, in both right and left side of the main patch antenna. This patch and parasitic element was designed by using Perfect Electrical Conductor (PEC) material. The ground of this antenna also fully designed by PEC. Other than that, on parasitic element has consisted shorting pin. This pin designed to make the beam direction change from center position to the left or right side. Lastly, this antenna is be designed and analyzed by using CST Studio Suite Software. The basic parameter of an antenna such as reflection coefficient, gain and efficiency.